2014
DOI: 10.1371/journal.pone.0095174
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Evolutionary History Affect Survival in Stressful Environments

Abstract: The world is increasingly impacted by a variety of stressors that have the potential to differentially influence life history stages of organisms. Organisms have evolved to cope with some stressors, while with others they have little capacity. It is thus important to understand the effects of both developmental and evolutionary history on survival in stressful environments. We present evidence of the effects of both developmental and evolutionary history on survival of a freshwater vertebrate, the rough-skinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 89 publications
(119 reference statements)
2
21
0
Order By: Relevance
“…Gadow (1901) stated that ''Common salt is poison to the Amphibia,'' and there is no doubt that amphibians are indeed osmotically challenged organisms due to their permeable skin and eggs (Shoemaker and Nagy 1977). A plethora of studies have found that salt can lead to increased mortality, developmental deformities, physiological stress, and the alteration of growth and development at (e.g., Ely 1944;Ruibal 1959;Beebee 1985;Padhye and Ghate 1992;Viertel 1999;Turtle 2000;Chinathamby et al 2006;Dougherty and Smith 2006;Collins and Russell 2009;Karraker and Ruthig 2009;Langhans et al 2009;Chambers 2011;Duff et al 2011;Harless et al 2011;Alexander et al 2012;Hopkins et al 2013a,b;Hua and Pierce 2013) and across different life-history stages (i.e., carry-over effects; Petranka and Doyle 2010;Wu et al 2012;Hopkins et al 2014). This general intolerance has been demonstrated repeatedly (and as such will not be a focus of this review) and, perhaps as a result, there are no truly marine-or salinespecialist amphibian species.…”
mentioning
confidence: 99%
“…Gadow (1901) stated that ''Common salt is poison to the Amphibia,'' and there is no doubt that amphibians are indeed osmotically challenged organisms due to their permeable skin and eggs (Shoemaker and Nagy 1977). A plethora of studies have found that salt can lead to increased mortality, developmental deformities, physiological stress, and the alteration of growth and development at (e.g., Ely 1944;Ruibal 1959;Beebee 1985;Padhye and Ghate 1992;Viertel 1999;Turtle 2000;Chinathamby et al 2006;Dougherty and Smith 2006;Collins and Russell 2009;Karraker and Ruthig 2009;Langhans et al 2009;Chambers 2011;Duff et al 2011;Harless et al 2011;Alexander et al 2012;Hopkins et al 2013a,b;Hua and Pierce 2013) and across different life-history stages (i.e., carry-over effects; Petranka and Doyle 2010;Wu et al 2012;Hopkins et al 2014). This general intolerance has been demonstrated repeatedly (and as such will not be a focus of this review) and, perhaps as a result, there are no truly marine-or salinespecialist amphibian species.…”
mentioning
confidence: 99%
“…Larvae that experienced 7°C during embryonic development did not grow as large or as developed as larvae in the other embryonic treatments, regardless of larval temperature. This inability to compensate for a "bad start" also occurs in amphibians exposed to osmotic stress during embryonic development (Hopkins et al, 2014;Wu et al, 2012). An exception to this pattern occurred at larval temperature 7°C, where larval growth (but not development) was equally slow regardless of embryonic temperature ( Fig.…”
Section: Discussionmentioning
confidence: 89%
“…These effects resulted in altered swimming performance, which has important survival implications (Watkins and Vraspir, 2006). Considering that smaller, less developed larvae are more susceptible to pollution (Beebee, 1986;Cooke, 1979;Hopkins et al, 2014) and predators (Anderson et al, 2001;Boone et al, 2002;Gall et al, 2011;Touchon et al, 2013;Warkentin, 1995), the carry-over effects of embryonic temperature in salamanders and newts could have survival consequences in later life stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations